Lewis acid-catalyzed chemodivergent and regiospecific reaction of phenols with quaternary peroxyoxindoles - Shaikh, Moseen A.; Samal, Pragnya Paramita; Ubale, Akash S.; Krishnamurty, Sailaja; Gnanaprakasam, Boopathy (Journal of Organic Chemistry, 2022)
The indium-catalyzed regiospecific coupling of substituted phenol derivatives and quaternary peroxyoxindoles for the synthesis of C2 or C4 benzoxazin-3-one-substituted phenols via skeletal rearrangement is described. This reaction is demonstrated with 17 examples with good yields and diverse aryl substituents. In contrast to the indium-catalyzed reaction, the Cu(OTf)2- catalyzed reaction of the phenol with quaternary peroxyoxindoles afforded C2 or C4 2-oxindole-substituted phenol derivatives. This diverse catalytic reaction generated various biologically important phenol-substituted 2-oxindole derivatives directly without any skeleton rearrangement and was demonstrated with 19 examples in high yield. The regiospecificity and the reaction pathways were explained with the support of density functional theory (DFT).